Офтальмологічні критерії синдрому недиференційованої дисплазії сполучної тканини у дітей з набутою міопією - Цибульська, Таміла Євгенівна; Завгородня, Т. С.; Цибульская, Т. Е.; Завгородняя, Т. С.; Tsybulska, T. E.; Zavgorodnya, T. S. (ИД "Заславский", 2019)
Метою роботи було визначення офтальмологічних критеріїв синдрому недиференційованої дисплазії сполучної тканини у дітей з набутою міопією. Встановлено, що головними офтальмологічни- ми критеріями зорового аналізатора, які дозволяють проводити дискримінацію при набутій міопії між наявністю синдрому недиференційованої дисплазії сполучної тканини та його відсутністю з точками порогу класифікації, є показник заломлюючої сили рогівки ≤ 41,5 дптр (чутливість 88 %, специфічність 90 %), глибина передньої камери ока ≥ 3,88 мм (чутливість 87 %, специфічність 78 %), діаметр рогівки ≥ 11,85 мм (чутливість 90 %, специфічність 87 %). Целью работы было определение офтальмологических критериев синдрома недифференцированной дисплазии соединительной ткани у детей с приобретенной миопией. Установлено, что главными офтальмологическими критериями зрительного анализатора, которые позволяют проводить дискриминацию при приобретенной миопии между наличием синдрома недифференцированной дисплазии соединительной ткани и его отсутствием с точками порога классификации, являются показатель преломляющей силы роговицы ≤ 41,5 дптр (чувствительность 88 %, специфичность 90 %), глубина передней камеры глаза ≥ 3,88 мм (чувствительность 87 %, специфичность 78 %), диаметр роговицы ≥ 11,85 мм (чувствительность 90 %, специфичность 87 %). Dysplasia of connective tissue is a factor contributing to the development of myopia, the incidence of which in children with CNDS at the age of 7–16 years old ranges from 36.2 % to 79.2 %. The purpose of the research is to determine the ophthalmologic criteria for syndrome of undifferentiated connective tissue dysplasia in children with acquired myopia. The ophthalmologic examination was performed on 44 children (88 eyes) with myopia and syndrome of undifferentiated connective tissue dysplasia (group I) and on 40 children (80 eyes) with myopia and without syndrome of undifferentiated connective tissue dysplasia (group II). Groups were representative by age and clinical refraction. The phenotypic signs of connective tissue dysplasia were assessed according to the diagnostic criteria of T. Milkovska-Dimitrova and A. Karkasheva. The method of discriminant analysis was used to determine the variables that allow classify the study groups. Results. Among 15 parameters analyzed, which included the main anatomical and functional data of the visual analyzer by the stepwise exclusion method, 7 factors were selected to be analyzed using a discriminant method, namely refractive corneal force, anterior chamber depth, radius, corneal diameter, coronary hysteresis, average thickness of the layer of peripapillary nerve fibers, axial length of the eye. It has been established, that the main ophthalmologic criteria of the visual analyzer that allow discrimination in acquired myopia between the presence of syndrome of undifferentiated connective tissue dysplasia and its absence with the threshold points, are the corneal refractive index ≤ 41.5 dp (sensitivity 88 %, specificity 90 %), the anterior chamber depth ≥ 3.88 mm (sensitivity 87 %, specificity 78 %), corneal diameter ≥ 11.85 mm (sensitivity 90 %, specificity 87 %). The data obtained may be useful in the comprehensive assessment of ophthalmic manifestations of the syndrome of undifferentiated connective tissue dysplasia, in the prognosis of the development of the myopic process and in determining of the individual treatment tactics.
Офтальмологические критерии синдрома недифференцированной дисплазии соединительной ткани у детей с приобретенной миопией
Ophthalmic criteria for syndrome of undifferentiated connective tissue dysplasia in children with acquired myopia
Keywords: міопія; діти; офтальмологічні маркери; дисплазія сполучної тканини; дискримінантний аналіз; миопия; дети; офтальмологические маркеры; дисплазия соединительной ткани; дискриминантный анализ